THE RELATIONSHIP OF SELF COMPASSION AND RESILIENCE IN FINAL LEVEL STUDENTS AT THE FACULTY OF HEALTH SCIENCES AS-SYAFI'IYAH ISLAMIC UNIVERSITY - Ambarwati Dia Permatasari; Zuhriya Meilita (Afiat, 2022)
Final year students are required to write a thesis, when compiling a thesis they are faced with various obstacles and difficulties that can make students depressed so that it has an impact on students' psychology, therefore resilience is needed. Resilience is a person's ability to rise, endure, adapt to difficult conditions. Resilience is influenced by self-acceptance and being kind to oneself or what is called self-compassion. The purpose of the study was to determine the relationship between self- compassion and resilience in final year students at the Faculty of Health Sciences, As-Syafi'iyah Islamic University. The research method is descriptive correlation with cross sectional design. The sample in this study is purposive sampling with a total of 50 samples. Data collection by using a questionnaire. The data analysis technique used univariate (%) and bivariate using chi-square (X2) to see the relationship between self-compassion and resilience in final year students. The result of this research is the p value of Asym. Sig. (2-sided) Chi-Square obtained p value Asym. Sig. (2- sided) = 0.041 this value is smaller than = 5% (0.05), then H0 is rejected, students have high self- esteem (36.0%) and high resilience (38.0%). The conclusion is that there is a relationship between self-compassion and resilience in final year students at the Faculty of Health Sciences, As-Syafi'iyah Islamic University. The researcher's suggestion is that final year students can maintain their self- compassion and resilience by discussing with friends, praying to Allah SWT, motivating themselves, getting up and accepting yourself in difficult circumstances.